A European Market for Malian Mangoes - Mohan, P.C. (World Bank, Washington, DC, 2012)
In 2001 a pilot operation to export mangoes from Mali was set up as part of the new operation plan of the Agro-Processing Trading Project (Projet d'Appui ?a Valorisation et Commercialisation des Produits Agricoles - PAVCOPA), financed by the World Bank. The objective of the project was to provide technical support to the Agricultural Trading and Processing Promotion Agency (Agence pour la Promotion des Fili?s Agricoles - APROFA), a non-profit, government-funded agency responsible for providing marketing opportunities for smallholders' agricultural products. The pilot operation set an unprecedented experience in establishing a multi-modal shipment system connecting the Malian Southern town of Sikasso to Abidjan and improving every step of the supply-chain (from production to packaging) in order to export mangoes grown by Malian smallholders to Northern Europe. The operation was highly successful and led to its expansion in the subsequent years.